Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1099/mic.0.2007/005942-0
|View full text |Cite
|
Sign up to set email alerts
|

Acid-shock responses in Staphylococcus aureus investigated by global gene expression analysis

Abstract: A general overview is presented of the changes in the genetic expression along a time curve through the first 20 min after acidification to pH 4.5 of exponentially growing cultures of the food pathogenic strain Staphylococcus aureus 50583. A newly developed method for statistical significance testing was used to detect significant gene expression responses. Most responses showed an increase or decrease from time zero to 10 min after acidification, and then generally a stabilization in expression level from 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
137
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(156 citation statements)
references
References 55 publications
19
137
0
Order By: Relevance
“…Regarding MDR transporters, the most noticeable change in expression was that of norA, the drug transporter gene SACOL2460, and the bicyclomicin resistance gene bcr, all of which decreased at least 3-fold after 30 min at pH 4.5. In contrast, the genes encoding the NorC efflux pump and the EmrB/QacA drug transporter showed increases in their transcript titers of at least 10-fold after 20 min at pH 4.5 (2,5). These data for norA are consistent with our findings, but there are no prior data on acid stress response of norB, encoding the NorB efflux pump, or mgrA and norG, encoding transcriptional regulators of the Nor pumps.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Regarding MDR transporters, the most noticeable change in expression was that of norA, the drug transporter gene SACOL2460, and the bicyclomicin resistance gene bcr, all of which decreased at least 3-fold after 30 min at pH 4.5. In contrast, the genes encoding the NorC efflux pump and the EmrB/QacA drug transporter showed increases in their transcript titers of at least 10-fold after 20 min at pH 4.5 (2,5). These data for norA are consistent with our findings, but there are no prior data on acid stress response of norB, encoding the NorB efflux pump, or mgrA and norG, encoding transcriptional regulators of the Nor pumps.…”
Section: Discussionsupporting
confidence: 79%
“…These adaptations are multifaceted, involving changes in expression of many genes with various functions, but the specific mechanisms are not well studied. The acid stress response has been shown to include increased transcript levels of genes involved in utilization of urease (ureA, ureB, ureC, and ureF) and of nuoF, which encodes an NADH dehydrogenase, which can increase internal cell pH by assisting proton export from the bacterial cell (1,2,5,6,28). A decrease in transcripts encoding the F 0 F 1 ATPase was also observed, which was somewhat surprising since this F 0 F 1 ATPase is considered an important proton extrusion mechanism in several Gram-positive bacterial species, such as Streptococcus mutans (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…crtN encodes squalene synthase, an enzyme involved in carotenoid biosynthesis (41). recA and rexA encode enzymes involved in various DNA repair functions (21,51,52). We also selected an additional three genes associated with basic metabolism and cell division functions (gapA, ftsZ, and pta); these genes, along with sodA and recA, were analyzed to determine appropriate reference genes for the oxic and anoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus among other pathogens is destroyed by pH lower than 5 (Medveďová and Valík, 2012). However, emerging research has shown that some strains of E. coli can survive the low pH (Gran et al, 2003;Bore et al, 2007). A combination of harsh conditions and prolonged exposure time has been said to result in microbes building some adaptation mechanism (Lucking et al, 2013).…”
Section: Introductionmentioning
confidence: 99%